The Influence of Work Motivation and Job Stress on Job Satisfaction of XYZ Jombang High School Teachers - Vina Fauziah; Wisnu Mahendri (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to determine the influence of work motivation and work stress on the job satisfaction of XYZ Jombang High School teachers. The population in this study was 31 teachers, while the sample was 31 respondents using saturated sampling techniques. The data was collected using a questionnaire method, which was then analyzed using multiple regression analysis using SPSS version 26. The results of the research showed that partially work motivation had a positive and significant effect on job satisfaction, while the work stress variable had a negative and significant effect on job satisfaction. Simultaneously, the variables of work motivation and work stress influence the job satisfaction of XYZ Jombang High School teachers. The results of the coefficient of determination analysis obtained 0.166 or 16.6%, which means that the contribution of work motivation and work stress variables to job satisfaction is 16.6%, while the remainder is influenced by other factors outside this regression model.